2021
DOI: 10.1089/acm.2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

“To Be Finally at Peace with Myself”: A Qualitative Study Reflecting Experiences of the Meditation-Based Lifestyle Modification Program in Mild-to-Moderate Depression

Abstract: Author Contributions: HCB and PS conceptualized and designed the study. JV, JG were involved in the acquisition of data. KM and PS supervised the data analysis. JV, JG, HCB, and KM contributed to qualitative analysis and reporting. HCB wrote the first draft of the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…With respect to MBLM, the additive effects of the ethics modules on postural yoga and meditation has already been shown in healthy participants (Matko et al, 2021). In a feasibility study with depressive patients and in the qualitative evaluation for a subgroup of patients in the present study, the ethical component of MBLM was identified as a key factor in individual empowerment and appreciation of one's own strengths (Bringmann et al, 2021a; Bringmann et al, 2021). Another difference between MBLM and TAU, which could explain the contrast in efficacy, was the dosage of therapy.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…With respect to MBLM, the additive effects of the ethics modules on postural yoga and meditation has already been shown in healthy participants (Matko et al, 2021). In a feasibility study with depressive patients and in the qualitative evaluation for a subgroup of patients in the present study, the ethical component of MBLM was identified as a key factor in individual empowerment and appreciation of one's own strengths (Bringmann et al, 2021a; Bringmann et al, 2021). Another difference between MBLM and TAU, which could explain the contrast in efficacy, was the dosage of therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, participants reported an increased capacity for self‐reflection, mindfulness, and self‐regulation. These results could be confirmed in a subsequent qualitative analysis, in which the high relevance of the ethical aspects for the participants and the associated reappraisal of their lives became apparent (Bringmann et al, 2021). Various components of MBLM also increased well‐being and reduced stress in psychologically healthy participants (Matko et al, 2021).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the reasons for this could be that the standard treatment caused more stress to patients in general than the MBLM program, which is based on positive psychology and aimed at achieving greater harmonization. In a qualitative analysis of the MBLM program compared to standard treatment, evidence was found that the MBLM program was subjectively experienced as more coherent and more tailored to individual needs than the standard therapy ( 33 ), indicating a source of stress that might have influenced HRV parameters–at least during the first 8 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the aforementioned frameworks, the program equally serves neurocognitive and neurophysiological processes for eudaimonic wellbeing. The program has been shown to be feasible and effective for depressive outpatients ( 33 , 34 ). In healthy individuals participating in the MBLM program, incremental and differential effects of practicing various components of the program could be seen, supporting the relevance of multilayered processes as described above ( 35 ).…”
Section: Introductionmentioning
confidence: 99%